Experiment and numerical modeling suspended ceiling with identification of working diagram material (Fracture and Structural Integrity, 2016)
The aim of this topic is to describe creating of working diagrams of structural materials. These will be used as input parameters for nonlinear analysis of real structures. Working diagrams of construction material are derived from experimental tensile tests and numerical analysis. We will use construction steel in this case. Derived working diagrams are used as an input parameter for numerical modelling of real structures. They are also used as a comparison with data from realized physical tests. Numerical modelling is based on 3D model of structure and it takes into account physical and geometrical nonlinearities.
Keywords: Experiment; Numerical modelling; Working diagrams; Analysis; Finite element method